The Impact of Action Video Game Training on Mathematical Abilities in Adults - Melissa E. Libertus; Allison Liu; Olga Pikul; Theodore Jacques; Pedro Cardoso-Leite; Justin Halberda; Daphne Bavelier (SAGE Publishing, 2017)
Playing action video games has previously been linked to improvements in attentional control, the ability to choose what to attend and what to ignore that relies on a frontoparietal network of the brain. Here we asked whether action video game training would impact a range of mathematical abilities that rely on similar brain regions. Twenty-four adults completed extensive cognitive testing before, after 25 hr, and after 40 hr of video game training. Half of the participants trained on an action video game, the other half trained on a nonaction video game. Action video game training yielded no significant improvements in foundational number-processing skills and attentional control in this study but some improvements on standardized assessments of complex mathematics. Thus, although action video game play is clearly not an intervention of choice when considering mathematical skills, the present study suggests its use as a recreational activity may support, albeit weakly, complex mathematical skills.